Low oral dose of 4-methylumbelliferone reduces glial scar but is insufficient to induce functional recovery after spinal cord injury - Štepánková, Kateřina; Chudíčková, Milada; Šimková, Zuzana; Martinez-Varea, Noelia; Kubinová, Šárka; Urdzíková, Lucia Machová; Jendelová, Pavla; Kwok, Jessica C F (Scientific reports, 2023)
Spinal cord injury (SCI) induces the upregulation of chondroitin sulfate proteoglycans (CSPGs) at the glial scar and inhibits neuroregeneration. Under normal physiological condition, CSPGs interact with hyaluronan (HA) and other extracellular matrix on the neuronal surface forming a macromolecular structure called perineuronal nets (PNNs) which regulate neuroplasticity. 4-methylumbelliferone (4-MU) is a known inhibitor for HA synthesis but has not been tested in SCI. We first tested the effect of 4-MU in HA reduction in uninjured rats. After 8 weeks of 4-MU administration at a dose of 1.2 g/kg/day, we have not only observed a reduction of HA in the uninjured spinal cords but also a down-regulation of CS glycosaminoglycans (CS-GAGs). In order to assess the effect of 4-MU in chronic SCI, six weeks after Th8 spinal contusion injury, rats were fed with 4-MU or placebo for 8 weeks in combination with daily treadmill rehabilitation for 16 weeks to promote neuroplasticity. 4-MU treatment reduced the HA synthesis by astrocytes around the lesion site and increased sprouting of 5-hydroxytryptamine fibres into ventral horns. However, the current dose was not sufficient to suppress CS-GAG up-regulation induced by SCI. Further adjustment on the dosage will be required to benefit functional recovery after SCI.
Keywords: Spinal Cord; Rats; kyselina hyaluronová; poranění míchy; zvířata; chondroitinsulfát proteoglykany; Chondroitin Sulfate Proteoglycans; Hyaluronic Acid; hymekromon; mícha; Spinal Cord Injuries; Gliosis; krysa rodu Rattus; Hymecromone; glióza; Animals